Pathogen Screening for Possible Causes of Meningitis/Encephalitis in Wild Carnivores From Saxony-Anhalt - Höche, Jennifer; House, Robert Valerio; Heinrich, Anja; Schliephake, Annette; Albrecht, Kerstin; Pfeffer, Martin; Ellenberger, Christin (Frontiers in Veterinary Science, 2022)
Inflammation in meninges and/or brains are regularly noticed in red foxes and other wild carnivores during rabies control programs. Despite negative rabies virus (RABV) results, the etiologies of these cases remain unknown. Thus, the aim of this study was to provide an overview of the occurrence of pathogens that may cause diseases in brains of wild carnivores and pose a risk to humans and other animals. In addition to RABV and canine distemper virus (CDV), a variety of pathogens, including members of Flaviviridae, Bornaviridae, Herpesviridae, Circoviridae, as well as bacteria and parasites can also cause brain lesions. In 2016 and 2017, brain samples of 1124 wild carnivores were examined by direct fluorescent antibody test for RABV as well as (reverse-transcriptase) quantitative polymerase chain reaction for the presence of CDV as part of a monitoring program in Saxony-Anhalt, Germany. Here, we applied similar methods to specifically detect suid herpesvirus 1 (SuHV-1), West nile virus (WNV), Borna disease virus 1 (BoDV-1), canid alphaherpesvirus 1 (CaHV-1), canine parvovirus type 2 (CPV-2), fox circovirus (FoxCV) and Neospora caninum. Further, bacteriogical examination for the existence of Listeria monocytogenes and immunohistochemistry of selected cases to detect Toxoplasma gondii antigen were performed. Of all pathogens studied, CDV was found most frequently (31.05%), followed by FoxCV (6.80%), CPV-2 (6.41%) and Toxoplasma gondii (4/15; 26.67%), nematode larvae (1.51%), Listeria monocytogenes (0.3%) and various other bacterial pathogens (1.42%). In 68 of these cases (6.05%), multiple pathogen combinations were present simultaneously. However, RABV, WNV, BoDV-1, SuHV-1, CaHV-1 and Neospora caninum were not detected. The majority of the histopathological changes in 440 animals were inflammation (320/440; 72.73%), predominantly non-suppurative in character (280/320; 87.50%), and in many cases combined with gliosis, satellitosis, neuronophagia, neuronal necrosis and/or vacuolization/demyelination or in single cases with malacia. Thus, it could be shown that wild carnivores in Saxony-Anhalt are carriers mainly for CDV and sometimes also for other, partly zoonotic pathogens. Therefore, the existing monitoring program should be expanded to assess the spill-over risk from wild carnivores to humans and other animals and to demonstrate the role of wild carnivores in the epidemiology of these zoonotic pathogens.